1994
DOI: 10.3109/17453679409000907
|View full text |Cite
|
Sign up to set email alerts
|

Intercondylar notch width and the risk for anterior cruciate ligament rupture: A case-control study in 46 female handball players

Abstract: We measured the intercondylar notch of the femur in female handball players from radiographs of 20 players with previous unilateral anterior cruciate ligament injury, and 26 controls without injury. The groups were comparable regarding age, height, weight and level of performance. Intercondylar fossa radiographs were obtained in a posteroanterior axial position. The anterior opening of the intercondylar notch was narrower in the healthy knee of the injured group compared to the controls. There was an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
0
8

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 11 publications
4
94
0
8
Order By: Relevance
“…Our finding that a lower NWI index may predispose to ACL injury in the paediatric population is in accordance with previous studies looking at young adult populations [2][3][4][5][6][7]20]. While there is still disagreement in the literature as to whether variations in notch geometry related to differences in gender or limb dominance, play a contributing role in ACL injuries, we did not find a difference in NWI with respect to gender, involved side, mechanism of injury or type of sport engaged in at the time of injury [7,12,13,18,21,22].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Our finding that a lower NWI index may predispose to ACL injury in the paediatric population is in accordance with previous studies looking at young adult populations [2][3][4][5][6][7]20]. While there is still disagreement in the literature as to whether variations in notch geometry related to differences in gender or limb dominance, play a contributing role in ACL injuries, we did not find a difference in NWI with respect to gender, involved side, mechanism of injury or type of sport engaged in at the time of injury [7,12,13,18,21,22].…”
Section: Discussionsupporting
confidence: 82%
“…This difference may be caused by different imaging techniques used for the evaluation of NWI. Two studies measuring NWI using MRI [8,21] have shown much higher values for normal adult populations than values reported in radiographic studies [2][3][4][5][6][7]20].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations